Food insecurity and depression: a cross‐sectional study of a multi‐site urban youth cohort in Durban and Soweto, South Africa. Issue 6 (25th March 2021) - Jesson, Julie; Dietrich, Janan; Beksinska, Mags; Closson, Kalysha; Nduna, Mzikazi; Smit, Jenni; Brockman, Mark; Ndung'u, Thumbi; Gray, Glenda; Kaida, Angela
Abstract: Objective: To assess the prevalence of food insecurity and the independent association between depression and food insecurity among youth living in two urban settings in South Africa. Methods: Baseline cross‐sectional survey data was analysed from a prospective cohort study conducted between 2014 and 2016 among youth (aged 16–24 years) in Soweto and Durban. Interviewer‐administered questionnaires collecting socio‐demographic, sexual and reproductive health and mental health data were conducted. Household food insecurity was measured using the 3‐item Household Hunger Scale, with food insecure participants defined as having 'moderate' or 'severe hunger' compared to 'no hunger'. Depression was assessed using the 10‐item Center for Epidemiological Studies Depression (CES‐D 10) Scale (range 0–30, probable depression ≥ 10). Multivariable logistic regression models were used to estimate the association between depression and food insecurity. Results: There were 422 participants. Median age was 19 years (interquartile range [IQR] 18–21) and 60% were women. Overall, 18% were food insecure and 42% had probable depression. After adjustment for socio‐demographic variables (age, gender, female‐headed household, household size and school enrolment), participants with probable depression had higher odds of being food insecure than non‐depressed participants (2.79, 95%CI 1.57–4.94). Conclusion: Nearly one‐fifth of youth in this study were food insecure. Those with probable depression had increased odds of food insecurity. Interventions are needed to address food insecurity among urban youth in South Africa, combining nutritional support and better access to quality food with mental health support.